Sensitivity and specificity of clinical features used in Alvarado scoring system - Mahato, IP; Bhandari, R; Rajbhandari, R; Kumari, S; Yadav, AK (Health Renaissance, 2011)
Introduction: Alvarado score is one of the scoring systems for diagnosis of appendicitis. Objective: To assess the sensitivity and specificity of clinical features used in Alvarado score. Subjects and methods: A prospective study of 171 patients with pain in the right iliac fossa presenting to emergency at BPKIHS, Dharan, Nepal was conducted. The sensitivity and specificity of clinical features and lab parameters used in Alvarado score were evaluated comparing with final diagnosis based on operative and histopathological findings. Results: The sensitivity of clinical parameter were: migrating right iliac fossa pain- 99.1%, anorexia- 45.7%, nausea/vomiting- 73.7%, right iliac fossa tenderness- 100%, fever- 24.5%, rebound tenderness in right iliac fossa- 89.8%, leucocytosis (>10,000)- 84.7% and a neutrophilic shift to the left (>75%)- 68.6%. The specificity of clinical parameters were: migrating right iliac fossa pain- 45.3%, anorexia- 86.7%, nausea/vomiting- 54.7%, right iliac fossa tenderness- 1.8%, fever- 81.1%, rebound tenderness in right iliac fossa- 64.1%, leucocytosis (>10,000)- 83.1% and a neutrophilic shift to the left (>75%)- 71.6%. Conclusion: Migrating right iliac fossa pain, right iliac fossa tenderness and rebound tenderness in right iliac fossa had a high sensitivity, leucocytosis (>10,000) had both high sensitivity and high specificity. Thus, in our set up, use of Alvarado score appears helpful for diagnosis of appendicitis Keywords: Alvarado score; sensitivity; specificity DOI: 10.3126/hren.v9i1.4355 Health Renaissance, 2011: Vol.9 No.1:12-14